Analysis of the Relationship Between Sea Surface Temperature, Chlorophyll-a, and Spanish Mackerel (Scomberomorus Commerson) Catch in the Java Sea - Widodo, Nabila Azzahro; Susanto, AB; Suryono, Suryono (Jurnal Ilmiah Multidisipin, 2025)
Pati regency is a coastal area that contributes significantly to Indonesia’s fisheries sector. One if its major fishing ports, PPP Bajomulyo, serves as a hub for fishing activities, with catches ranging from small to large pelagic fish, including Spanish mackerel (Scomberomorus commerson). This study aims to examine to relationship between oceanographic parameters and Spanish mackerel catch volumes at PPP Bajomulyo over the 2021-2023 period. A survey-based approach incorporating satellite image overlay was employed. The analysis of non-linier relationships between variables was conducted using Generalized Additive Model (GAM), implemented in RStudio. Satellite image processing was performed using SeaDAS, while spatial analysis was carried out in ArcGIS. The findings reveal that the interaction between sea surface temperature (SST) and chlorophyll-a concentrations accounted for 11,44% oof catch variability. Elevated SST above 29,5 °C were associated with increased catch rates, whereas extreme temperature (>35 °C or <28 °C) corresponded with significant declines. Chlorophyll-a exerted a relativity weak influence on catch, suggesting that although it serves as a proxy for primary productivity, Spanish mackerel distribution is more strongly governed by thermal conditions and prey availability. The study further identified that optimal fishing grounds were predominantly located in northern Central Java waters, particularly during seasons characterized by favorable oceanographic conditions.